1986
DOI: 10.1177/000992288602501002
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Brucellosis in Childhood

Abstract: Two hundred children with brucellosis are described. The clinical characteristics on presentation included prolonged fever, arthralgia, weight loss, and malaise in the majority of the patients. Biochemical characteristics included a relative lymphocytosis in 92.9 percent of the patients and elevated liver enzymes in 83.5 percent. The Brucella agglutination titer was 1:320 or more in all the cases studied, but repeated blood cultures yielded growth of Brucella organisms in only 42 percent of the patients. Bruce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 12 publications
7
29
0
Order By: Relevance
“…Akbayram et al [40] reported isolated thrombocytopenia in some patients with brucellosis, and bone morrow aspiration revealed increased megakaryopoiesis in two of these five patients and thrombocytopenia reversed with medical treatment. Isolated thrombocytopenia may occur in brucellosis even in patients with active bone marrow and is improved by medical treatment [2,3,5,[36][37][38][39][40]. But change in platelet parameters between pre and post treatment periods was not clearly explained in those studies [2,3,5,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 95%
“…Akbayram et al [40] reported isolated thrombocytopenia in some patients with brucellosis, and bone morrow aspiration revealed increased megakaryopoiesis in two of these five patients and thrombocytopenia reversed with medical treatment. Isolated thrombocytopenia may occur in brucellosis even in patients with active bone marrow and is improved by medical treatment [2,3,5,[36][37][38][39][40]. But change in platelet parameters between pre and post treatment periods was not clearly explained in those studies [2,3,5,[36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 95%
“…B. melitensis, which produces more intense symptoms than the other Bru cella spp. [1], was identified in 12 patients out of the 13 with positive cultures, con forming to other series from Kuwait [3,4], The most commonly affected regions of the musculoskeletal system were the hip, knee and lumbosacral spine usually with the in volvement of one or two joints. The clinical picture is often intially confused with other forms of arthritis.…”
mentioning
confidence: 60%
“…Fever of unknown origin (FUO) is a common initial diagnosis in patients in areas of low endemicity 7 . Constitutional symptoms of brucellosis include anorexia, asthenia, fatigue, weakness, and malaise, and weight loss and are ve ry common (> 90% of cases).…”
Section: Clinical Features 331 Incubation Period-1week To Several Mmentioning
confidence: 99%